Regional working in the East of England: using the UK National Standards for Public Involvement - Mathie, Elspeth (Res Involv Engagem, 2018)
PLAIN ENGLISH SUMMARY: Involving patients and members of the public to help shape and carry out research is recommended in health research in the United Kingdom (UK). There are a number of regional networks of Patient and Public Involvement (PPI) groups, which support the collaboration between researchers, patients and public members. We are a group of researchers, patients and public members who came together via a PPI regional network in the East of England to collaborate on a research study about the extent of feedback from researchers to PPI contributors. The aim of this paper is to use the recently developed UK National Standards for Public Involvement to structure our thinking about what worked well and what did not, within our recently completed study. We believe this paper is one of the first to use the National Standards to structure a retrospective reflection on PPI within a study. Our findings showed that there are benefits of regional working, including easier access to public members and bringing together researchers, public members and those who run PPI groups for research collaboration. The main challenges included involvement of people before studies are funded and working across organisations with different payment processes. The National Standards for Public Involvement has provided a useful framework to consider how best to involve patients and members of the public in research and could be a helpful structure to reflect on successes and challenges in individual projects and also regional, national or international comparisons of PPI in research. ABSTRACT: Background Regional networks of Patient and Public Involvement (PPI) organisations, including academic institutions, health and social care services, charities, patient and public groups and individuals, can play an important part in carrying out health research. In the UK, recommendations by the National Institute of Health Research (NIHR) encourage the use of regional, collaborative networks with shared resources and training. Methods The newly developed UK National Standards for Public Involvement were used as a framework for a retrospective reflection of PPI within a recently completed research study which focused on feedback from researchers to PPI contributors. PPI contributors, those running PPI groups (PPI leads) and researchers involved in the study have contributed to this reflection by completing evaluation forms throughout the research alongside notes of meetings and co-authors’ final reflections. Results Results revealed a number of successes where the regional network was particularly useful in bringing together PPI contributors, those who lead PPI groups and researchers. The regional network helped researchers to get in touch with patients and members of the public. Challenges included involving people before funding and bureaucratic and financial barriers when working across different organisations in the region. The importance of working together in flexible, informal ways was key and on-going support for the PPI contributors was vital for continued involvement, including emotional support not just monetary. The first four National Standards of inclusive opportunities, working together, support and learning and communications were particularly useful as means of structuring our reflections. Conclusions To our knowledge, this is one of the first research studies to use the UK National Standards for Public Involvement as a framework to identify what worked well and the challenges of PPI processes. It is suggested that as more reflective papers are published and the National Standards are more widely used in the UK, many lessons can be learnt and shared on how to improve our Patient and Public Involvement within research studies. Evaluations or reflections such as these can further enhance our understanding of PPI with implications for regional, national and international comparisons.